SYNCHRONIZATION OF THE POTENTIAL OF INDUSTRIAL WORLD WITH SCHOOL PROFILES VOCATIONAL TO IMPROVE QUALITY AND CAPABILITY GRADUATES OF VOCATIONAL SCHOOLS IN INDONESIA - Amat Mukhadis; Nurul Ulfatin; Andika Bagus Nur Rahma Putra (Jurnal Ilmu Pendidikan, 2018)
Abstract: Synchronization of the Potential of Industrial World with School Profiles Vocational to Improve Quality and Capability Graduates of Vocational Schools in Indonesia. This study aims to map: (1) the potential of the business and industry that has the opportunity to collaborate with vocational fields; (2) profile of vocational field school (SMK) business in improving the quality of education; and (3) synchronizing the potential of the industrial world with the business profile of the SMK. This research was conducted using qualitative methods. The research location was centered in the East Java region with samples divided into three regions, namely the northern region, the southern region, and the eastern region. This study reveals that: (1) the industrial world has the opportunity to establish cooperation with vocational schools, namely the handicraft industry, food processing, creative arts, engineering technology, processed seafood, and materials; (2) priority programs for Vocational Schools in East Java include: improvement in special expertise, school-based enterprise programs, demand-market-driven programs, hands on experience programs, production based education programs, on-the-job teacher training programs, on the job programs student training, classical indoor and outdoor programs, training to be entrepreneur programs, and center test recruitment programs; and (3) synchronizing the map of the potential of the industrial world that has the opportunity to establish cooperation with vocational schools with a profile of Vocational Schools is very necessary because it can improve the quality and capability of vocational graduates.